Design, Synthesis, and Biological Evaluation of N-Acyl-Homoserine Lactone Analogs of Quorum Sensing in Pseudomonas aeruginosa - Wei, Zhenyu; Li, Ting; Gu, Yan; Zhang, Qian; Wang, Enhui; Li, Wenbo; Wang, Xin; Li, Yang; Li, Hongyu (Frontiers in Chemistry, 2022)
Quorum sensing plays a necessary role in the production of virulence factors and the formation of biofilm on Pseudomonas aeruginosa. Thus, the development of inhibition of quorum sensing is one of the most promising methods to control bacterial infection and antibiotic resistance. In this work, nine novel AHL analogs were designed, synthesized, and evaluated as potential quorum sensing inhibitors. The results depicted that structural modifications have significant effects on quorum sensing inhibition activity of AHL molecules. Without inhibiting the growth of P. aeruginosa, 2-(4-bromophenyl)-N-(2-oxotetrapyridinefuran-3-yl) butanamide (compound no.10) showed the excellent performance in inhibiting biofilm formation and virulence factor production among all the compounds through robustly suppressing the expression of QS related genes. In a molecular docking study, compound no.10 exhibited a higher affinity toward LasR than other AHL analogs. In addition, compound no.10 also exhibits the best inhibition effect on virulence production in the Caenorhabditis elegans infection model.